2008
DOI: 10.1002/ptr.2697
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of flavonoids and sesquiterpenoids from Achillea millefolium s.l. on cultured human tumour cell lines

Abstract: The antiproliferative activities of n-hexane, chloroform, aqueous-methanol and aqueous extracts of the aerial parts of the Achillea millefolium aggregate on three human tumour cell lines were investigated by means of MTT assays. The chloroform-soluble extract exerted high tumour cell proliferation inhibitory activities on HeLa and MCF-7 cells, and a moderate effect on A431 cells; accordingly, it was subjected to detailed bioactivity-guided fractionation. As a result of the multistep chromatographic purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 19 publications
6
59
0
Order By: Relevance
“…Its therapeutic properties are due to volatile compounds, phenols, and flavonoids in the plant extract. According to phytochemical studies, over 30 various terpenes and terpenoids have been identified in fennel (3), and compounds such as oestragol (methyl chavicol), fenchone, trans-anethol, and α-phellandrene are the main constituents of the fennel seed (19). The presence of flavonoids, cumarin, and anethole has been also identified.…”
Section: Introductionmentioning
confidence: 99%
“…Its therapeutic properties are due to volatile compounds, phenols, and flavonoids in the plant extract. According to phytochemical studies, over 30 various terpenes and terpenoids have been identified in fennel (3), and compounds such as oestragol (methyl chavicol), fenchone, trans-anethol, and α-phellandrene are the main constituents of the fennel seed (19). The presence of flavonoids, cumarin, and anethole has been also identified.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that casticin induced apoptotic cell death in p53 mutant or null breast cancer cell lines (Haidara et al, 2006) and in p53 mutated human cervical cancer HeLa cells (Csupor-Loffler et al, 2009;Chen et al, 2011a). Many studies have been carried out to supports the notion that cells with wild-type p53 exhibit increased sensitivity to radiation or chemotherapeutic agents and revealed that cells with mutant p53 sequence tends to exhibit less growth inhibition in the screen than the wild-type p53 cell lines when treated with the majority of clinically used anticancer agents including DNA cross-linking agents, anti-metabolites, and topoisomerase I and II inhibitors (O'Connor et al, 1997).…”
Section: Targeting Cancer Cells By Regulating Apoptosis Related Proteinsmentioning
confidence: 97%
“…As shown in Figure 1, accumulated data indicate that casticin was isolated from many plant species such as, namely Vitex agnus castus (Choudhary et al, 2009;Mesaik et al, 2009;Webster et al, 2011;Righeschi et al, 2012;Hogner et al, 2013), Daphne genkwa (Xie et al, 2011), Achillea millefolium (Haidara et al, 2006;Csupor-Loffler et al, 2009), Ficus microcarpa , Vitex rotundifolia (Ono et al, 2002;Hu et al, 2007b;Shen et al, 2009;Ye et al, 2010;Koh et al, 2011), Fructus viticis (Hu et al, 2007b;Guan et al, 2010;Chen et al, 2011b;Yang et al, 2011;Zeng et al, 2012;Zhou et al, 2013a), Vitex negundo (Diaz et al, 2003;Kunwar et al, 2010;Velpandian et al, 2013), Crataegus pinnatifida (Kao et al, 2005), Pavetta crassipes (Mali and Dhake, 2011), Nelsonia canescens, Butea frondosa Koen , Dalbergia odorifera (Mali and Dhake, 2011), Bryonia laciniosa (Aggarwal et al, 2011), Citrus unshu (Mali and Dhake, 2011;Nagoor et al, 2011), Centipeda minima (Mali and Dhake, 2011), Clausena excavate (Manosroi et al, 2005), Croton betulaster (de Sampaio e Spohr et al, 2010;Freitas et al, 2011), Dimorphandra mollis (Freitas et al, 2011), Artemisia abrotanum L. (Hernandez et al, 1999), Artemisia annua L …”
Section: Natural Sources Of Casticinmentioning
confidence: 97%
“…earlier tested against human tumour cell lines (Csupor-Löffler et al, 2009). High cell proliferation inhibitory activity was recorded for many extracts, which drew our attention to the investigation of other, not well-known species of the Centaurea genus.…”
Section: Biebersteini C Jacea and C Spinulosa) Native To Middle Anmentioning
confidence: 99%